Distinct types of foragers in the ant Ectatomma ruidum: typical foragers and furtive thieves. (November 2015) - McGlynn, Terrence P.; Graham, Russell; Wilson, Jane; Emerson, Jeremy; Jandt, Jennifer M.; Jahren, A. Hope
Abstract : A principal benefit of social living is the communal defence of resources. However, in the ant Ectatomma ruidum, specialized thieves often circumvent detection by conspecific non-nestmates, and those detected are peacefully expelled. Colonies can gather food through typical foraging (opportunistically tracking prey or nutrients in the home range) or by robbing (entering a conspecific nest, waiting for, and then removing a newly arrived food item carried in by a forager). Here, we conducted behavioural assays to determine whether robbers (or 'thieves'), carrying purloined food, manifest behaviours that minimize the probability of detection relative to nonthieving individuals. We found several lines of evidence that individuals carrying stolen food behave distinctly from normal nonthieving foragers. When returning to their home nest with a stolen food item, thieves had fewer encounters with conspecifics, were more likely to pause during movement, and were more likely to release food when grasped. Thieves walked faster while travelling in the victim's home range, compared to their own home range. When experimentally perturbed, thieves were more likely to reverse their direction of movement, while normal foragers continued moving in the same direction. Because the carbon and nitrogen stable isotope composition, as well as the C:N ratio, was the same for both thieves and nonthieves, we conclude that both groups were accessing the same food sources, using different behaviours to repartition a common resource. We conclude that, although thieves are morphologically indistinguishable from nonthieving foragers, their food retrieval behaviours are distinct in a manner that reduces the probability of detection and aggressive interactions with other conspecifics. We propose that thieves are a distinct caste of forager in E. ruidum . Highlights: Colonies of the ant Ectatomma ruidum have thieves that remove food from neighbouring colonies. Thieves behave differently than nonthieves; encounters with other ants are less frequent. Thieves of E. ruidum are a distinct behavioural caste, heretofore not described in ants.